Preparation method of high-strength, recoverable and repairable rapid light-curing bio-based adhesive

By combining cellulose with specific compounds and using ultraviolet curing technology, high-strength, recyclable and repairable bio-based adhesives are prepared, which solves the problem of difficulty in recycling traditional adhesives and high energy consumption, and achieves green and environmentally friendly adhesive preparation.

CN119505765AActive Publication Date: 2025-02-25NANJING FORESTRY UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311047832.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-25
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

Traditional synthetic adhesives are difficult to degrade or recycle, resulting in environmental pollution, and the curing process requires long-term heating, resulting in energy consumption.

Method used

By combining cellulose with compounds such as methacrylate and diisocyanate, cellulose-based macromonomers containing dynamic steric urea bonds are prepared, and quickly cured by ultraviolet curing technology to prepare high-strength, recyclable and repairable bio-based adhesives.

Benefits of technology

It realizes high strength, rapid photocuring and excellent recycling and repairability of bio-based adhesives, reduces energy consumption, reduces environmental pollution, and meets the requirements of the green development strategy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505765A_ABST
    Figure CN119505765A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength, recoverable and repairable rapid light-curing bio-based adhesive, which comprises the following steps: step 1, preparing a high-strength, recoverable, repairable and rapid light-curing bio-based adhesive; the preparation method comprises the following steps: dissolving cellulose, 2-(tert-butylamino) ethyl methacrylate, diisocyanate and a catalyst in a good solvent according to a certain molar ratio, and reacting at 40-100 DEG C for 2-8 hours to prepare a cellulose-based macromonomer containing dynamic steric hindrance urea bonds; and 2, dissolving the cellulose-based macromonomer, metacrylic acid ester and a photoinitiator in a good solvent according to a certain mass ratio, pouring the solution into a mold, and after the solvent is volatilized, carrying out ultraviolet curing for 1-10 minutes to prepare the high-strength, recoverable and repairable rapid photocuring bio-based adhesive. According to the preparation method, the green, environment-friendly, high-strength, recoverable and repairable rapid light-curing bio-based adhesive can be simply, conveniently and efficiently prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-strength, recyclable, repairable, fast-light-curing bio-based adhesive. Background Art

[0002] Adhesives are a type of polymer material that can combine two or more materials through interfacial adhesion and cohesion. They have been widely used in packaging, construction, electronics, medical and health fields, and are an indispensable bonding material in daily life. There are many types of adhesives that have been developed. According to their sources, they can be divided into natural adhesives and synthetic adhesives. Compared with natural adhesives, synthetic adhesives have the advantages of clear structural definition and adjustable functions, which can effectively improve the bonding strength of adhesives and give adhesives specific functions such as corrosion resistance and anti-aging. However, most of the raw materials for the production of traditional synthetic adhesives come from petrochemical products, making them difficult to degrade or recycle, thus causing a large amount of waste pollution. At the same time, most traditional adhesives require long-term heating during the curing process, resulting in a large amount of energy consumption. Therefore, the preparation of high-strength and fast-curing bio-based adhesives with recyclability can effectively reduce energy consumption, extend the service life of adhesives, and solve environmental pollution problems.

[0003] As the world's most abundant biomass resource, cellulose has the advantages of being environmentally friendly, inexpensive, and having multiple active hydroxyl groups. It has been widely used in synthetic plastics, coatings, rubber substitutes, inks, and insulating materials, and has the prospect of replacing some petroleum fossil resources. The polyhydroxy structure of cellulose can easily introduce various active groups or dynamic covalent bonds into cellulose through chemical modification, making it suitable for the construction of recyclable, repairable, and fast-curing bio-based adhesives. At the same time, the rigid molecular skeleton of cellulose can effectively improve the strength of bio-based adhesives, realizing the preparation of high-strength bio-based adhesives with green and sustainable development.

[0004] Therefore, by preparing high-strength, recyclable, repairable fast-photocuring bio-based adhesives, the problems of non-renewable, serious environmental pollution and high energy consumption in traditional synthetic adhesives can be solved, which is of great significance for the further development of green and environmentally friendly high-strength, recyclable, repairable fast-photocuring bio-based adhesives. Summary of the invention

[0005] Purpose of the invention: One of the purposes of the present invention is to provide a high-strength, recyclable, repairable, fast-light-curing bio-based adhesive. The bio-based adhesive not only has excellent bonding strength and fast light-curing ability, but also has excellent reprocessing ability, which not only improves the practical value of bio-based adhesives, but also meets the requirements of the "dual carbon" strategy; the second purpose of the present invention is to provide a method for preparing a high-strength, recyclable, repairable, fast-light-curing bio-based adhesive, which has the characteristics of simple operation, mild reaction conditions and good repeatability.

[0006] Technical solution: The high-strength, recyclable, repairable, fast-light-curing bio-based adhesive described in the present invention has a general structural formula as shown below:

[0007]

[0008] Among them, R is a characteristic functional group of cellulose, which is H or any one of -CH3, -CH2CH3, -CH2COOH, -COCH3, -CH2CH2OH, -CH2CH2CH2OH, R1 is a structural unit of diisocyanate, and R2 is a structural unit of methacrylate.

[0009] The present invention also provides a method for preparing a high-strength, recyclable, repairable, fast-light-curing bio-based adhesive, comprising the following steps:

[0010] (1) cellulose, 2-(tert-butylamino)ethyl methacrylate, diisocyanate, and a catalyst are reacted in a good solvent at a certain molar ratio at 40 to 100° C. for 2 to 8 hours to prepare a cellulose-based macromolecular monomer containing a dynamic hindered urea bond;

[0011] (2) A cellulose-based macromolecular monomer, methacrylate, and photoinitiator are dissolved in a good solvent in a certain mass ratio and poured into a mold. After the solvent evaporates, the mixture is cured under ultraviolet light for 1 to 10 minutes to prepare a high-strength, recyclable, and repairable fast-photocuring bio-based adhesive.

[0012] In the above step (1), the molar ratio of cellulose, 2-(tert-butylamino)ethyl methacrylate, diisocyanate and catalyst is [cellulose]:[2-(tert-butylamino)ethyl methacrylate]:[diisocyanate]:[catalyst]=1:1-7:1-4:0.05-0.2.

[0013] Among them, cellulose is any one of methyl cellulose, ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose acetate, microcrystalline cellulose, and nanocellulose; diisocyanate is any one of diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate; the catalyst is any one of stannous octoate and dibutyltin dilaurate; and the good solvent is any one of N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, N,N-dimethylacetamide / lithium chloride, toluene, and tetrahydrofuran.

[0014] In the above step (2), the mass ratio of cellulose-based macromonomer, methacrylate and photoinitiator is [cellulose-based macromonomer]: [methacrylate]: [photoinitiator] = 1: 0.5-3: 0.02-0.1.

[0015] Wherein, the methacrylate is any one of methyl methacrylate, lauryl methacrylate, tetrahydrofurfuryl methacrylate, furfuryl methacrylate, and hydroxyethyl methacrylate; the photoinitiator is any one of 2-hydroxy-2-methylpropiophenone and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide; and the good solvent is any one of N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, N,N-dimethylacetamide / lithium chloride, toluene, and tetrahydrofuran.

[0016] Beneficial effects:

[0017] (1) The method for preparing a high-strength, recyclable, repairable, fast-photocuring bio-based adhesive of the present invention has the characteristics of simple operation and good repeatability, and can prepare a high-strength, recyclable, repairable, fast-photocuring bio-based adhesive.

[0018] (2) The high-strength, recyclable, repairable, fast-photocuring bio-based adhesive of the present invention can be used as a new type of bio-based adhesive. In addition to having excellent mechanical properties and fast photocuring capabilities, it also has excellent recyclability and repairability, meets the requirements of the green development strategy, and is suitable for a wider range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the infrared spectra of ethyl cellulose and ethyl cellulose macromer in Example 1.

[0020] Figure 2 1 is the uniaxial tensile stress-strain curve of the ethyl cellulose-based adhesive before and after recovery in Example 1.

[0021] Figure 3The bonding strength curve of the ethyl cellulose-based adhesive used for bonding glass substrates in Example 1 is DETAILED DESCRIPTION

[0022] The present invention is further described in detail below with reference to examples.

[0023] The raw materials and reagents in the following examples are all commercially available.

[0024] Example 1: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using ethyl cellulose

[0025] The first step: dissolving ethyl cellulose, 2-(tert-butylamino)ethyl methacrylate, diphenylmethane diisocyanate, and stannous octoate in a molar ratio of [ethyl cellulose]:[2-(tert-butylamino)ethyl methacrylate]:[diphenylmethane diisocyanate]:[stannous octoate]=1:3:2:0.1 in toluene and reacting at 50°C for 8h to prepare a dynamic hindered urea bond-containing ethyl cellulose macromonomer;

[0026] The second step: dissolving ethyl cellulose macromer, tetrahydrofurfuryl methacrylate, and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide in toluene at a mass ratio of [ethyl cellulose macromer]: [tetrahydrofurfuryl methacrylate]: [diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide] = 1:0.5:0.05, and then pouring the mixture into a mold, and curing the mixture under ultraviolet light for 10 minutes after the toluene evaporates, to prepare a high-strength, recyclable, repairable, fast-light-curing ethyl cellulose-based adhesive.

[0027] Figure 1 The infrared spectra of ethyl cellulose and ethyl cellulose macromonomer in Example 1 are shown in FIG. 3319 cm -1 and 1637cm -1 The peaks at the two ends correspond to the amide and vinyl absorption peaks of the ethyl cellulose macromonomer, respectively, indicating the successful preparation of ethyl cellulose macromonomer containing dynamic hindered urea bonds that can be rapidly photocured.

[0028] Figure 2 1 is the uniaxial tensile stress-strain curve of the ethyl cellulose-based adhesive before and after recycling in Example 1. It can be seen from the figure that the adhesive has excellent mechanical properties before and after recycling, and the recovery efficiency of mechanical strength reaches 89.4%, indicating that the adhesive has high strength and good recyclability and repairability.

[0029] Figure 3 This is the bonding strength curve of the ethyl cellulose-based adhesive used for bonding a glass substrate in Example 1. It can be seen from the figure that the bonding strength of the glass substrate bonded by the adhesive can reach 64 MPa, indicating that the adhesive has excellent bonding ability.

[0030] Example 2: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using methyl cellulose

[0031] The first step: dissolving methyl cellulose, 2-(tert-butylamino)ethyl methacrylate, diphenylmethane diisocyanate, and stannous octoate in a molar ratio of [methyl cellulose]:[2-(tert-butylamino)ethyl methacrylate]:[diphenylmethane diisocyanate]:[stannous octoate]=1:1:1:0.05 in tetrahydrofuran and reacting at 40°C for 8h to prepare a methyl cellulose macromonomer containing a dynamic hindered urea bond;

[0032] The second step: dissolving methylcellulose macromer, tetrahydrofurfuryl methacrylate, and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide in tetrahydrofuran at a mass ratio of [methylcellulose macromer]: [tetrahydrofurfuryl methacrylate]: [diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide] = 1:1:0.1, and then pouring the mixture into a mold, and curing the mixture with ultraviolet light for 5 minutes after the tetrahydrofuran evaporates, to prepare a high-strength, recyclable, repairable, fast-light-curing methylcellulose-based adhesive.

[0033] Example 3: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using carboxymethyl cellulose

[0034] The first step: dissolving carboxymethyl cellulose, 2-(tert-butylamino)ethyl methacrylate, isophorone diisocyanate, and dibutyltin dilaurate in a molar ratio of [carboxymethyl cellulose]:[2-(tert-butylamino)ethyl methacrylate]:[isophorone diisocyanate]:[dibutyltin dilaurate]=1:5:3:0.15 in dichloromethane and reacting at 80°C for 3h to prepare a carboxymethyl cellulose macromonomer containing a dynamic hindered urea bond;

[0035] Step 2: Dissolve carboxymethyl cellulose macromer, methyl methacrylate and 2-hydroxy-2-methylpropiophenone in dichloromethane at a mass ratio of [carboxymethyl cellulose macromer]: [methyl methacrylate]: [2-hydroxy-2-methylpropiophenone] = 1:3:0.1, pour the mixture into a mold, and after the dichloromethane evaporates, cure it under ultraviolet light for 2 minutes to prepare a high-strength, recyclable and repairable fast-light-curing carboxymethyl cellulose-based adhesive.

[0036] Example 4: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using microcrystalline cellulose

[0037] The first step: dissolving microcrystalline cellulose, 2-(tert-butylamino)ethyl methacrylate, hexamethylene diisocyanate, and dibutyltin dilaurate in a molar ratio of [microcrystalline cellulose]:[2-(tert-butylamino)ethyl methacrylate]:[hexamethylene diisocyanate]:[dibutyltin dilaurate]=1:2:2:0.1 in an N,N-dimethylacetamide / lithium chloride system and reacting at 40°C for 6h to prepare a microcrystalline cellulose macromonomer containing a dynamic hindered urea bond;

[0038] Step 2: dissolve microcrystalline cellulose macromer, glycidyl methacrylate, and 2-hydroxy-2-methylpropiophenone in dichloromethane at a mass ratio of [microcrystalline cellulose macromer]:[glycidyl methacrylate]:[2-hydroxy-2-methylpropiophenone]=1:2:0.05, and pour the mixture into a mold. After the dichloromethane evaporates, cure the mixture under ultraviolet light for 3 minutes to prepare a high-strength, recyclable, repairable, fast-light-curing microcrystalline cellulose-based adhesive.

[0039] Example 5: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using nanocellulose

[0040] The first step: dissolving nanocellulose, 2-(tert-butylamino)ethyl methacrylate, lysine diisocyanate, and stannous octoate in a molar ratio of [nanocellulose]:[2-(tert-butylamino)ethyl methacrylate]:[lysine diisocyanate]:[stannous octoate]=1:7:4:0.2 in N,N-dimethylformamide and reacting at 100°C for 2h to prepare a nanocellulose macromonomer containing a dynamic hindered urea bond;

[0041] Step 2: Dissolve nanocellulose macromer, lauryl methacrylate, and 2-hydroxy-2-methylpropiophenone in tetrahydrofuran at a mass ratio of [nanocellulose macromer]: [lauryl methacrylate]: [2-hydroxy-2-methylpropiophenone] = 1:2:0.1, pour the mixture into a mold, and after the tetrahydrofuran evaporates, cure it under ultraviolet light for 5 minutes to prepare a high-strength, recyclable, repairable, fast-light-curing nanocellulose-based adhesive.

[0042] Example 6: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using hydroxyethyl cellulose

[0043] The first step: dissolving hydroxyethyl cellulose, 2-(tert-butylamino)ethyl methacrylate, diphenylmethane diisocyanate, and stannous octoate in a molar ratio of [hydroxyethyl cellulose]:[2-(tert-butylamino)ethyl methacrylate]:[diphenylmethane diisocyanate]:[stannous octoate]=1:2:1:0.1 in N,N-dimethylformamide and reacting at 50°C for 4h to prepare a hydroxyethyl cellulose macromonomer containing a dynamic hindered urea bond;

[0044] Step 2: Dissolve hydroxyethyl cellulose macromer, furfuryl methacrylate and 2-hydroxy-2-methylpropiophenone in dimethyl sulfoxide at a mass ratio of [hydroxyethyl cellulose macromer]: [furfuryl methacrylate]: [2-hydroxy-2-methylpropiophenone] = 1:3:0.2, and pour into a mold. After the dimethyl sulfoxide evaporates, cure under ultraviolet light for 10 minutes to prepare a high-strength, recyclable, repairable, fast-light-curing hydroxyethyl cellulose-based adhesive.

[0045] Example 7: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using cellulose acetate

[0046] The first step: dissolving cellulose acetate, 2-(tert-butylamino)ethyl methacrylate, hexamethylene diisocyanate, and stannous octoate in a molar ratio of [cellulose acetate]:[2-(tert-butylamino)ethyl methacrylate]:[hexamethylene diisocyanate]:[stannous octoate]=1:3:2:0.1 in N,N-dimethylformamide and reacting at 60°C for 4h to prepare a cellulose acetate macromonomer containing a dynamic hindered urea bond;

[0047] Step 2: Dissolve cellulose acetate macromer, hydroxyethyl methacrylate, and 2-hydroxy-2-methylpropiophenone in N,N-dimethylformamide at a mass ratio of [cellulose acetate macromer]:[hydroxyethyl methacrylate]:[2-hydroxy-2-methylpropiophenone]=1:1:0.05, pour the mixture into a mold, and after N,N-dimethylformamide evaporates, cure under ultraviolet light for 4 minutes to prepare a high-strength, recyclable, repairable, fast-light-curing cellulose acetate-based adhesive.

[0048] Example 8: Preparation of high-strength, recyclable, repairable, fast-light-curing bio-based adhesive using hydroxypropyl cellulose

[0049] The first step: dissolving hydroxypropyl cellulose, 2-(tert-butylamino)ethyl methacrylate, dicyclohexylmethane diisocyanate, and dibutyltin dilaurate in a molar ratio of [hydroxypropyl cellulose]:[2-(tert-butylamino)ethyl methacrylate]:[dicyclohexylmethane diisocyanate]:[dibutyltin dilaurate]=1:4:2:0.15 in toluene and reacting at 80°C for 4h to prepare a hydroxypropyl cellulose macromonomer containing a dynamic hindered urea bond;

[0050] Step 2: Dissolve hydroxypropyl cellulose macromer, furfuryl methacrylate and 2-hydroxy-2-methylpropiophenone in toluene at a mass ratio of [hydroxypropyl cellulose macromer]: [furfuryl methacrylate]: [2-hydroxy-2-methylpropiophenone] = 1:1.5:0.1 and pour into a mold. After the toluene evaporates, cure under ultraviolet light for 10 minutes to prepare a high-strength, recyclable, repairable, fast-light-curing hydroxypropyl cellulose-based adhesive.

[0051] Tests have shown that the high-strength, recyclable, repairable, fast-photocuring bio-based adhesives prepared in Examples 1 to 8 above have high strength and can be recycled through reprocessing, thereby extending the service life of the bio-based adhesive and expanding the application field of the bio-based adhesive.

Claims

1. A high-strength, recyclable, repairable, fast-curing bio-based adhesive, characterized in that The general structure is as follows Wherein, R is a characteristic functional group of cellulose, which is any one of H or -CH3, -CH2CH3, -CH2COOH, -COCH3, -CH2CH2OH, -CH2CH2CH2OH, R1 is a structural unit of diisocyanate, and R2 is a structural unit of methacrylate; The method for preparing the high-strength, recyclable, repairable, fast-light-curing bio-based adhesive comprises the following steps: (1) Cellulose, 2-(tert-butylamino)ethyl methacrylate, diisocyanate, and a catalyst are reacted in a good solvent at a certain molar ratio at 40-100° C. for 2-8 hours to prepare a cellulose-based macromonomer containing a dynamic hindered urea bond, wherein the cellulose, 2-(tert-butylamino)ethyl methacrylate, diisocyanate, and catalyst are reacted in a certain molar ratio of cellulose: 2-(tert-butylamino)ethyl methacrylate: diisocyanate: catalyst = 1: 1-7: 1-4: 0.05-0.2, and the cellulose is methyl cellulose, ethyl cellulose, or carboxymethyl cellulose. any one of cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose acetate, microcrystalline cellulose, and nanocellulose; the diisocyanate is any one of diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate; the catalyst is any one of stannous octoate and dibutyltin dilaurate; the good solvent is any one of N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, N,N-dimethylacetamide / lithium chloride, toluene, and tetrahydrofuran; (2) A cellulose-based macromer, methacrylate, and photoinitiator are dissolved in a good solvent in a certain mass ratio and poured into a mold. After the solvent evaporates, the mixture is cured under ultraviolet light for 1 to 10 minutes to prepare a high-strength, recyclable, repairable, fast-photocuring bio-based adhesive. The cellulose-based macromer, methacrylate, and photoinitiator are in a certain mass ratio of cellulose-based macromer: methacrylate: photoinitiator = 1: 0.5 to 3: 0.02 to 0.

1. The methacrylate is any one of methyl methacrylate, lauryl methacrylate, tetrahydrofurfuryl methacrylate, furfuryl methacrylate, and hydroxyethyl methacrylate. The photoinitiator is any one of 2-hydroxy-2-methylpropiophenone and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide. The good solvent is any one of N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, N,N-dimethylacetamide / lithium chloride, toluene, and tetrahydrofuran.

2. A method for preparing a high-strength, recyclable, repairable, fast-light-curing bio-based adhesive according to claim 1, characterized in that The following steps are involved: (1) Cellulose, 2-(tert-butylamino)ethyl methacrylate, diisocyanate, and a catalyst are reacted in a good solvent at a certain molar ratio at 40-100° C. for 2-8 hours to prepare a cellulose-based macromonomer containing a dynamic hindered urea bond, wherein the cellulose, 2-(tert-butylamino)ethyl methacrylate, diisocyanate, and catalyst are reacted in a certain molar ratio of cellulose: 2-(tert-butylamino)ethyl methacrylate: diisocyanate: catalyst = 1: 1-7: 1-4: 0.05-0.2, and the cellulose is methyl cellulose, ethyl cellulose, or carboxymethyl cellulose. any one of cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, cellulose acetate, microcrystalline cellulose, and nanocellulose; the diisocyanate is any one of diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and lysine diisocyanate; the catalyst is any one of stannous octoate and dibutyltin dilaurate; the good solvent is any one of N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, N,N-dimethylacetamide / lithium chloride, toluene, and tetrahydrofuran; (2) A cellulose-based macromer, methacrylate, and photoinitiator are dissolved in a good solvent in a certain mass ratio and poured into a mold. After the solvent evaporates, the mixture is cured under ultraviolet light for 1 to 10 minutes to prepare a high-strength, recyclable, repairable, fast-photocuring bio-based adhesive. The cellulose-based macromer, methacrylate, and photoinitiator are in a certain mass ratio of cellulose-based macromer: methacrylate: photoinitiator = 1: 0.5 to 3: 0.02 to 0.

1. The methacrylate is any one of methyl methacrylate, lauryl methacrylate, tetrahydrofurfuryl methacrylate, furfuryl methacrylate, and hydroxyethyl methacrylate. The photoinitiator is any one of 2-hydroxy-2-methylpropiophenone and diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide. The good solvent is any one of N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, N,N-dimethylacetamide / lithium chloride, toluene, and tetrahydrofuran.

Citation Information

Patent Citations

  • Lignin-based waterborne polyurethane-acrylate wood adhesive and preparation method thereof

    CN115466585A

  • Preparation and application of bio-based ultraviolet curing adhesive for wet-process laminated inductor production

    CN115477912A

  • Bio-based polyacrylate material as well as preparation method and application thereof

    CN115991852A

  • Isocyanate-waterborne hyperbranched multi-block copolymer composite emulsion adhesive and preparation method thereof

    CN116200151A

  • Ordinary temperature curable resin composition

    JP1992318014A